Sodium Butylated Hydroxytoluene (NaBHT) as a New and Efficient Hydride Source for Pd‐Catalysed Reduction Reactions. Issue 57 (19th September 2019) - Sharif, Sepideh; Rodriguez, Michael J.; Lu, Yu; Kopach, Michael E.; Mitchell, David; Hunter, Howard N.; Organ, Michael G.
Abstract: NaBHT (sodium butylated hydroxytoluene), a hindered and soluble base for the efficient arylation of various base‐sensitive amines and (hetero)aryl halides has been found to have an unanticipated role as a hydride donor to reduce (hetero)aryl halides and allylic acetates. Mechanistic studies have uncovered that NaBHT, but not BHT, can deliver multiple hydrides through oxidation of the benzylic methyl group in NaBHT to the aldehyde. Further, performing the reduction with NaBHT‐d20 has revealed that the redox‐active benzylic position is not the only hydride donor site from NaBHT with one hydride in three coming, presumably, from the tert‐ butyl groups. The reduction works well under mild conditions and, incredibly, only consumes 20 percent of the NaBHT in the process; the remaining 80 percent can be readily recovered in pure form and reused. This, combined with the low cost of the material in ton‐scale quantity, makes it practical and attractive for wider use in industry at scale. Abstract : New candidate : Sodium butylated hydroxytoluene (NaBHT) has been discovered to be a highly efficient, general reductant for the Pd‐catalysed reduction of (hetero)aryl halides and allylic acetates (see scheme). BHT is readily available on a multi‐ton scale at pennies per gram making this new reaction a potential candidate for large‐scale, fine‐chemical manufacturing.